Cannabinoids in the Treatment of Parkinson’s Disease - Gandor, Florin; Ebersbach, Georg (Neurology International Open, 2017)
Due to the changing legal status of medical cannabis and derivatives in numerous countries, this therapeutic option has moved into the field of public debate. Neurologists treating patients with idiopathic Parkinson’s disease are increasingly confronted with questions regarding cannabis as a treatment alternative, especially for levodopa-resistant Parkinson’s symptoms. A number of single case reports and case series suggested improvement of Parkinsonian symptoms after cannabinoid intake, but the small number of available randomized clinical trials failed to reproduce the extent of these findings. Only one trial found a reduction of levodopa-induced dyskinesia with cannabinoid treatment, the remaining three trials showed no effect on Parkinsonian symptoms. This article gives an overview on the effects of cannabis, and reviews experimental and clinical trials studying the effects of cannabinoids in idiopathic Parkinson’s disease.
Keywords: Parkinson’s disease; THC; cannabinoids